JEJAK BUDDHISME DALAM NOVEL KARYA KWEE TEK HOAY “BOENGA ROOS DARI TJIKEMBANG”: PERSPEKTIF FENOMENOLOGI - Yulianti Yulianti (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
In the first half of the 20th century, many Buddhist background texts were published, primarily by private publishers. One of the scriptwriters was a Chinese Peranakan named Kwee Tek Hoay (KTH). As a Chinese philosopher and philosopher, KTH has written many short stories, novels, and translations in the field of kebatinan. The article attempts to investigate Buddhism, especially Buddhist phenomena with a phenomenological paradigm in one of the KTH works entitled Boenga Roes from Tjikembang.